Análise da gestão do contrato de terceirização de limpeza da Universidade Federal de Santa Maria - Albarello, Sandro (2016)
The outsourcing process is a practice that is increasingly more present in the public organizations, what determined many changes in the kind of management because it transfers to thirty-party services the execution of intermediate activities from formalization of outsourcing contracts, enabling the public organizations to focus more on their final activities. In this perspective, the paper focused on the analysis of outsourcing contract management in the public administration and as main aim to examine how the elaboration processes, the cleaning outsourcing contract management and the inspection were configured at the Federal University of Santa Maria (UFSM). For this reason, they were adopted as investigation procedures the documental analysis to explain how the process happens; the bibliography analysis to make a theoretical basis about the researched theme, interviews with the people involved to verify how exactly happens the outsourcing contract management at UFSM. In a first moment, it was made the description about the cleaning services at the university. From this approach, it was analyzed how the outsourcing processes of cleaning services happen from the public notice elaboration to the supervision and inspection of contracts, permitting an analysis of all process. The results highlighted that there are several challenges in the contract management of cleaning services. The main challenges are the lack of professional qualification involved in the process, lack of standardization, failures at the contracts and difficulties of the university management. It was also identified that the UFSM is aware about the problems and that there is a discussion about the management improvement with professional qualification to those involved in the outsourcing contract processes and improvement of the contract processes and their inspection.